Creating Genetic System - Zahid, Zuhair R. (Journal of the Faculty of Medicine Baghdad, 2012)
Along with RNA and proteins, DNA is one of the three major macromolecules that are essential for all known forms of life. DNA is a long polymer of two helical chains, each measuring 2.2-2.6 nanometers (nm) and one nucleotide unit measuring 0.33 nm long. Although individual repeating unit is very small, DNA polymer, containing millions of nucleotides (approximately 220 million base pairing long (1,2).